FATORES ALIMENTARES ASSOCIADOS À OBESIDADE EM CRIANÇAS DE 0 A 2 ANOS DE IDADE: UMA REVISÃO NARRATIVA (REMUNOM, 2025)
The objective of this review is to analyze the dietary factors associated with obesity in Brazilian children aged 0 to 2 years. This is a narrative review in which 906 studies were initially identified in the databases. After reading titles and abstracts and applying inclusion and exclusion criteria, 11 studies were selected for analysis. The review gathered evidence from Brazilian studies published between 2018 and 2022 that address dietary factors associated with childhood obesity in this age group. The included studies had sample sizes ranging from 22 to 14,326 children. The results showed a high prevalence of inadequate dietary practices, with an emphasis on the early introduction of ultraprocessed foods before six months of age. Early cessation of exclusive breastfeeding was also identified, with the early introduction of other foods and liquids in the first months of life. This study highlighted that inadequate dietary practices in the first two years of life are strongly associated with the risk of childhood obesity in Brazil. The early introduction of ultraprocessed foods and weaning before six months, contrary to the recommendations for exclusive breastfeeding, are critical factors that compromise healthy growth and favor the development of chronic diseases throughout life.